Circulatory Support with Extracorporeal Membrane Oxygenation and/or Impella for Cardiogenic Shock During Myocardial Infarction. Issue 6 (November 2018) - Mourad, Marc; Gaudard, Philippe; De La Arena, Pablo; Eliet, Jacob; Zeroual, Norddine; Rouvière, Philippe; Roubille, François; Albat, Bernard; Colson, Pascal H.
Abstract : Temporary mechanical circulatory support (TCS) is recommended for patients with profound cardiogenic shock (CS). Extracorporeal membrane oxygenation (ECMO) and Impella are possible TCS devices, but the device choice and the implantation timing are not definitely established, specifically during acute myocardial infarction. We have analyzed the respective use of ECMO or Impella (2.5, CP, or 5.0) for CS following acute myocardial infarction, from a cohort of patients who underwent TCS within 72 hours after admission for emergency percutaneous coronary intervention (PCI) from January 2009 to April 2015. Among 88 TCS-treated patients, 42 had early TCS: 23 ECMO and 19 Impella. Cardiac management, including PCI, was similar between the two groups, but ECMO patients were sicker than Impella patients (higher blood lactate level at ICU admission, higher vasoactive-inotroic and ENCOURAGE scores before TCS implantation, p ⩽ 0.02). Three patients (7%) have had TCS implantation before admission, but TCS was implanted mostly in cathlab (43%, 1 during PCI, 13 just after PCI) or soon after ICU admission (50%, n = 21). Modification of the initial TCS choice was required in 10 cases (24%) for assistance upgrading in case of Impella (n = 4) or for left ventricle unloading in case of ECMO (n = 6). Extracorporeal membrane oxygenation is the technique of choice in case of profound CS, whereas Impella devices seem more appropriate for less severe hemodynamic compromise. Interestingly, the combination of both techniques may help to overcome the limits inherent to each device.